When Is It Democratically Legitimate to Opt Out of Public Education?. Issue 3 (18th August 2020) - Moses, Michele S.; Wilson, Terri S.
Abstract : In this essay, Michele Moses and Terri Wilson explore the recent movement to opt out of state tests. They situate this activism within a diverse line of efforts to refuse aspects of public education, asking how to evaluate the democratic legitimacy of different kinds of refusal in public education. Drawing on specific examples of opting out, they point to different ethical principles at stake in conflicts over public education. They pose three sets of questions — emphasizing reasons, positionality, and consequences — to help guide local educational leaders, policymakers, and citizens in negotiating difficult cases of refusal in public education. Moses and Wilson conclude that opting out of tests may, under certain conditions, serve the public purposes of education in a democratic society. Although many opt‐out activists justify their actions in terms of individual rights, others are concerned with public goals and ideals, including concerns about the narrowing of curriculum, the erosion of teacher authority, and the widening privatization of public education. Yet communicating across and between different interests in this movement remains a challenge, one that points to the need for spaces of democratic deliberation about the aims of education policy.